Be yourself or adapt yourself? Authenticity, self-monitoring, behavioural integrity, and trust. Issue 1 (2nd January 2022) - Nguyen, Brenda; Leroy, Hannes; Gill, Carol; Simons, Tony
Abstract : Prior work has offered good arguments to trust both authentic and self-monitoring individuals, yet these two constructs have been described as incompatible and even opposite. This tension raises the question of which strategy will best build trust: Be yourself or adapt yourself? Informed by theory on private and public selves at work, this paper argues that both self-monitoring and authenticity behaviours foster trust, but only when not accompanied by the other behaviour. While actors can combine authenticity and self-monitoring in their self-concept, observers see this combination as lacking behavioural integrity (i.e. word-deed misalignment), thus reducing trust. We test these relationships in a time-lagged, multi-source survey study with project teams. Our results support the hypothesis and demonstrate that behavioural integrity mediates the interaction between authenticity and self-monitoring on perceptions of trust. We discuss the implications of our findings for the development and implementation of effective trust-building strategies.